Development of a sample preparation approach for the analysis of fining agents in wines by liquid chromatography with tandem mass spectrometry. (15th July 2021) - Rodrigues Spinelli, Fernanda; Drehmer, Ana Paula; Valentin, Leonardo; Nascimento, Simone; Baptistão, Mariana; Vanderlinde, Regina
Highlights: Developed an improved sample preparation approach for protein analysis in wines. Optimized pH adjustments prior to sample preparation for improved protein recoveries. Optimized the sample preparation to improve the detection limits of proteins. LC-ESI-MS/MS method used to quantify different allergenic residues simultaneously. Abstract: During winemaking a wide variety of processing aids such as albumin, caseinates and lysozyme are often used. These proteins are considered allergenic and could become a human health risk in susceptible individuals. In our knowledge, there are no methods published for the analysis of these three proteins simultaneously by liquid chromatography with tandem mass spectrometry, with electrospray ionization. Therefore, in this work, a sample preparation approach for the analysis of α-casein, β-casein, albumin and lysozyme, in a single run, was performed and compared with published data. Through a pH adjustment, combining the use of cellulose ester membranes, a precipitation with organic solvents and a final concentration/clean-up, we achieved recovery values from 90.7 to 108.6%. The method was validated, showing determination coefficients R 2  ≥ 0.99. This method was able to quantify proteins even at lower levels (limits of quantification from 0.01 to 0.25 mg/L) than the current legal limits.